Artikel Analisis Sentimen terhadap Resolusi Genjatan Senjata PBB 2023: Studi pada 10 Negara Penolak Resolusi Konflik Israel-Palestina - Wirdayanti; Qofifa, Sitti Nurlaili; Ardiansyah, Rizka; Joefrie, Yuri Yudhaswana; Lapatta, Nouval Trezandy (The Indonesian Journal of Computer Science, 2024)
The Israeli-Palestinian conflict is the longest conflict that still has not found a bright spot. In December 2023 the UN again gave the latest resolution with the title “Armistice” this resolution received pros and cons from UN member states. The number of pro countries is 150 countries, contra as many as 10 countries and 23 countries abstain. This study aims to investigate whether the 10 countries that voted against the UN resolution represent the interests of their people or only represent the interests of their country. This research approach uses sentiment analysis on platform X with the Support Vector Machine method. Data was taken from March 2024 to the latest data, 137,447 data were obtained with 5 countries using non-English languages and 4 countries using English. Each data from these countries was successfully classified into positive and negative classes. The survey was conducted on 9 countries with an average positive sentiment of 34.82% and an average negative sentiment of 77.41%. The results of this research show that the decisions made by the 10 countries that rejected the resolution represent the voice of their people.